RECORRIDO HISTÓRICO SOBRE LA PERVERSIÓN. UNA ARQUEOLOGÍA DEL TÉRMINO EN EL PSICOANÁLISIS. - Soto Rodríguez, Mario Andrés (2012)
The meaning of pervertion is a historic construction. In this article there is a travel through distinct stages until the emergence of psychoanalysis, moment in which the Freudian work is reutilized to make an archaeology of the term, including several of his forms (sadism, masochism, fetishism and others) to make a mention of the input of Jaques Lacan in the psychoanalytic theory in this aspect.